PENGEMBANGAN SISTEM MANAJEMEN PENGETAHUAN UNTUK KERANGKA KERJA SISTEM INFORMASI AKUNTASI - Dana Indra Sensuse; Aryanto Aryanto (Paradigma, 2010)
Technological developments, especially the Internet, has resulted changes in transaction activities and business processes of an organization. Activities of transactions that required buyers and sellers meeting at a certain place and time can now be done without any limitation of space and time. Buyers are able to view, order products and make payments whenever and wherever she/he is. The seller can receive orders, check product availability, order packing, ship goods, and receive payment from a particular place without the need for face to face directly with the buyer. The transaction activities can be done if they are supported by a business environment, called the Electronic Network Business Environment (ENBE). In addition, the Electronic Network Business Environment (ENBE) also provides changes in the activities of the company's financial reporting. The field of accounting must be able to adjust to these changes. The Financial Accounting Standards (SAK) issued by IAI has gradually adjusted towards a changing business processes. Knowledge in the field of Accounting Information System design, including hardware, software, brainware, data and procedure are also experiencing change and development. This study aims to create a framework for designing accounting information systems in the era of the Electronic Networking Business Environment (ENBE) that can be used as a reference / guideline for developing a system. The KMS Development serves as a basis to create the framework for accounting information systems. A number of the KMS methods, such as capturing and sharing knowledge, are becoming a major discussion in this study. Data collection methods conducted in this study include qualitative methods, i.e., interview and action research. It is expected that this study is able to provide a good impact to people (especially accountants, programmers), process (efficiency and effectiveness), product quality, and ultimately organizational performance can be improved as a whole. Key Words: Knowledge Management Systems, Accounting Information System